Impact of the Swap It, Don't Stop It Australian National Mass Media Campaign on Promoting Small Changes to Lifestyle Behaviors. Issue 12 (1st December 2016) - O'Hara, Blythe J.; Grunseit, Anne; Phongsavan, Philayrath; Bellew, William; Briggs, Megan; Bauman, Adrian E.
Abstract : Mass media campaigns aimed at influencing lifestyle risk factors are one way that governments are attempting to address chronic disease risk. In Australia, a national campaign aimed at encouraging Australians to make changes in lifestyle-related behaviors was implemented from 2008 to 2011. The first phase, Measure Up (2008–2009), focused on why lifestyle changes are needed by increasing awareness of the link between waist circumference and chronic disease risk. The second phase, Swap It, Don't Stop It (2011), emphasized how adults can change their behaviors. Cross-sectional telephone surveys (after the campaign) were undertaken in July and November 2011 to evaluate the Swap It, Don't Stop It campaign and included measures of campaign awareness and lifestyle-related behavior change. Survey participants ( N = 5, 097) were similar across the two survey periods. Prompted campaign awareness was 62% (16% for unprompted awareness); females, younger respondents (18–44 years), those in paid employment, and those who spoke English at home were more likely to report prompted/unprompted campaign awareness. Moreover, 16% of survey respondents reported any swapping behavior in the previous 6 months, with the majority (14%) reporting only one swap; younger respondents and those in paid employment were significantly more likely to report having implemented a swapping behavior. The campaign achieved modest population awareness but demonstrated limited effect in terms of nudging behaviors. This evaluation indicates that encouraging swapping behaviors as a prelude to lifestyle change may not result from a mass media campaign alone; a comprehensive multicomponent population approach may be required.